The risk factors of laparoscopic and open repair surgery of inguinal hernia in a tertiary care center - Goenka, Ashish; Ijjapawar, Mahesh (International Surgery Journal, 2020)
Background: The purpose of the present study to investigate the incidence of inguinal hernia and risk factors of laparoscopic and open repair surgery. Methods: The present study contained 3 bilateral,17 right-sided and 7 left-sided hernia in the laparoscopic group and 2 bilateral, 19 right-sided and 6 left-sided hernia in open repair group. A total of 54 patients had an inguinal hernia, 27 underwent open repair and 27 underwent laparoscopic to open repair. Results: The age group of patients of open repair is 51-60 years, whereas 41-50 years in laparoscopic repair. The mean age was 47 years in open repair against 43 years in the laparoscopic repair. Conclusions: Among them, eight patients from open repair (1-COPD, 3-asthma,1-hypertension, 3-smoking) and five patients with the laparoscopic repair (2- COPD, 2-asthma, 1-hypertension) had one of the above-mentioned risk factors.